Deadlocks in Datacenter Networks: Why Do They Form, and How to Avoid Them - Hu, Shuihai; Zhu, Yibo; Cheng, Peng; Guo, Chuanxiong; Tan, Kun; Padhye, Jitu; Chen, Kai (HotNets-XV, 2016)
Driven by the need for ultra-low latency, high throughput and low CPU overhead, Remote Direct Memory Access(RDMA) is being deployed by many cloud providers. To deploy RDMA in Ethernet networks, Priority-based Flow Control(PFC) must be used. PFC, however, makes Ethernet networks prone to deadlocks. Prior work on deadlock avoidance has focused on necessary condition for deadlock formation, which leads to rather onerous and expensive solutions for deadlock avoidance. In this paper, we investigate sufficient conditions for deadlock formation, conjecturing that avoiding sufficient conditions might be less onerous.